Pengolahan Tanaman Singkong Menjadi Produk Es Krim Untuk Masyarakat Desa Kepek Kecamatan Saptosari Kabupaten Gunungkidul - Kristiawan, Yanuarius Benny (Jurnal Atma Inovasia, 2021)
Cassava or cassava is one of the largest food sources in Indonesia. Cassava is an alternative food that is rich in carbohydrates. In Kepek Village, Saptosari District, there are many crops produced from agriculture, namely rice, corn, cassava, peanuts, and soybeans. This journal will discuss the process of making ice cream with cassava-based ingredients, as well as a discussion of the mapping of village potentials owned by Kepek Village, Saptosari District. The method of making cassava ice cream is by utilizing the harvest products owned by Kepek Village, Saptosari District, by peeling and washing cassava. Then do soaking in water for 24 hours. Combine water, coconut milk, cornstarch, sugar, refined salt, sweetened condensed milk, and emulsifier in a saucepan. After that, the ice cream was put in the freezer for 24 hours with a temperature parameter of 4°C. The results of the development of making ice cream using cassava as a base ingredient can find out another effective and interesting process regarding the utilization of agricultural products, namely cassava.